Theory of multiphoton single and double ionization of two-electron atomic systems driven by short-wavelength electric fields: An ab initio treatment - EDAH, GASTON (My University, 2006)
We give a detailed account of an ab initio computational treatment of multiphoton single ionizationwith or without excitation as well as double ionization of two-electron atoms exposed to short-wavelength electric fields. This treatment is time dependent and based on a spectral method of configuration interaction type combined with Jacobi orJ-matrix calculations. It involves a complete treatment of electron-electron correlation in the initial and final states as well as during the time propagation. The atom eigenvalue problem is first solved by means of the spectral method. It consists of expanding the atom wave function in a basis of products of complex Coulomb-Sturmian functions of the electron radial coordinates and bipolar harmonics of the angular coordinates. This method allows a high-resolution study of many atomic states, in particular high-lying singly excited states as well as many doubly excited states. Results for He are presented and discussed in detail. The time-dependent Schrödinger equation is then solved by means of an explicit scheme of Runge-Kutta type. An accurate calculation of the probability of single and double ionization is carried out by projecting the ionizing wave packet on fully correlated multichannel scattering wave functions generated by means of theJ-matrix method. After a detailed analysis of the accuracy of this method, we show that our results for the total cross section of one-photon single and double ionization of He and H- are in very good agreement with those obtained by the most sophisticated approaches. Two-photon double ionization of He is then considered, and results are presented in a frequency regime where substantial discrepancies subsist between all existing calculations. Our results demonstrate that electron correlations in the final state play a significant role.
Keywords: Multiphoton; ionization; two-electron atomic systems